An analysis of taxi ratio in urban area using GIS - Ortiz-Zamora, Francisco José; Ladrón-de-Guevara-López, Isidro; Trujillo-Aguilera, Davinia; Blázquez-Parra, Elidia Beatriz (My University, 2018)
Urban development has started a change led by various factors: human impact on climate change, ageing population that is nowadays significant, increase of its density in urban environments, and processes of globalization that are promoted by incessant incorporation of new technologies. The Smarts cities have become a guinea pig for experimentation with new technologies, applying them to the mobility, infrastructures, energy or information. A focus of the new urban development model revolves around technology, and service needs depend more on the fact of having or being able to access to the specific data than the own available technology itself. Innovations in big data, free access to open data and cloud computing will affect urban development patterns. It is necessary to give substance to all that production, storage, processing and management of the data sources available: sensors, location and positioning systems, cloud computing, open data and communication networks. We proposes to add value to the data of the sources mentioned above, applied to public transport custom, in a city around 600.000 residents, through the GIS analysis of mobility patterns. Location and real time tracking of vehicles provide information on their status. It allows for taking decisions quickly and efficiently, and so on, establishing for example, mobility patterns. True challenge is to detect and transmit key information extracted from a huge volume of data, in which the public, private and business data must be combined effectively to achieve a more integrated knowledge of citizen habits in urban environment.
Keywords: Sistemas de información geográfica; Taxis; Movilidad